Simulation of a Stirling Engine with a Reversible Reaction CO + 2H2  CH3OH - K.О. Sabdenov; Zh.K. Smagulov; M. Erzada; T.A. Stryapchev (Қарағанды университетінің хабаршысы. Физика сериясы)
Using a simple computer model, the properties of a Stirling engine are studied, where the working substance is a chemically reacting gas with a reversible reaction CO + 2H2  CH3OH. The model takes into account the relaxation time of hydrodynamic processes in the regenerator. In this case, the engine is considered to consist of three main parts: a heater, regenerator and a cooler, this is fundamental difference from the Langlois Justin model proposed in 2006. The pressure in the engine is 20 MPa, the working piston is free. The efficiency is compared for two cases: 1) a reversible chemical reaction occurs in the working gas and 2) the working gas is chemically inert with relatively high and low molar mass. The average power over the oscillation period is several hundred watts, but the maximum power can reach 2 kW. To increase the power of an engine with reversible chemical reaction, it is necessary to increase the volume of the cooler and reduce the volume of the heater. The modeling results are in good agreement with the previously obtained theoretical results of one of the authors (K. Sabdenov, 2023) based on the analysis of the Stirling cycle with reversible chemical reaction.